PERAN KEPALA DESA DALAM MENGELOLA KEBERAGAMAN MASYARAKAT DESA SEKARAN KECAMATAN KAYEN KIDUL KABUPATEN KEDIRI - Nugroho, Timo Cahyo; Kustomo, Kustomo (JURNAL ILMU SOSIAL DAN ILMU POLITIK, 2025)
The village head is a government official who has the authority and duties to organize the village household and regional government. The problem that arises in the local wisdom of religious communities is that some people in Sekaran village do not yet have awareness of the importance of harmony. The aim of this research is to determine (1) social capital in managing religious diversity and 2) the role of village heads in managing religious diversity. The method used in this research is a type of qualitative research. Data collection techniques through observation, interviews and documentation. Data analysis techniques use data reduction, data presentation and conclusions. The results of the research show that (1) social capital in managing the diversity of religious communities, namely in order to build a harmonious and harmonious living atmosphere among people of the same religion, between religious communities and religious communities and the government, it is appropriate to use references from the theory of social capital (social capital) based on local wisdom values and (2) the role of the village head in managing religious diversity, namely the role of the village head to the community as a protector, protector and guarantor of the rights and obligations in carrying out worship in accordance with the beliefs of its citizens. It is important to discuss the role of the village head in managing religious diversity and it is hoped that the community can contribute to village activities and strive to preserve local wisdom values.